1988
DOI: 10.1073/pnas.85.4.1169
|View full text |Cite
|
Sign up to set email alerts
|

Old mice recover the ability to produce IgG and high-avidity antibody following irradiation with partial bone marrow shielding.

Abstract: The splenic plaque-forming-cell (PFC) response to trinitrophenylated bovine gamma globulin of 18-to 20-month-old mice is markedly depressed, with a preferential loss of indirect (IgG) PFC and high-avidity-antibody-secreting cells compared to 6-to 8-week-old animals. The antitrinitrophenyl response of old mice, whose peripheral lymphoid system has been reconstituted from their own bone marrow after irradiation while their bone marrow was partially shielded, includes high-avidity and IgG PFCs relatively comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…We suggested that the senescence of humoral immunity resulted from the influence of the long-lived peripheral T cells on the population of B cells emerging from the bone marrow. This conclusion was consistent with the re-expression of a "young-like" antibody repertoire in old mice whose peripheral T cells had been destroyed by lethal irradiation and whose immune system had been autoreconstituted from their own bone marrow thai had been shielded from radiation damage (10). We concluded ourreviewin 1989 by writing, "the alterations in the repertoire of ami body produced by old mice is not due to an intrinsic defect in the bone marron or in the B lymphocyle populations orisind from the bone marrow but ralher ID a selective downregulation by fluio-anti-idiotypic antibody which shift the idid type distribution of the peripheral B cell population" (7).…”
Section: Introductionsupporting
confidence: 79%
“…We suggested that the senescence of humoral immunity resulted from the influence of the long-lived peripheral T cells on the population of B cells emerging from the bone marrow. This conclusion was consistent with the re-expression of a "young-like" antibody repertoire in old mice whose peripheral T cells had been destroyed by lethal irradiation and whose immune system had been autoreconstituted from their own bone marrow thai had been shielded from radiation damage (10). We concluded ourreviewin 1989 by writing, "the alterations in the repertoire of ami body produced by old mice is not due to an intrinsic defect in the bone marron or in the B lymphocyle populations orisind from the bone marrow but ralher ID a selective downregulation by fluio-anti-idiotypic antibody which shift the idid type distribution of the peripheral B cell population" (7).…”
Section: Introductionsupporting
confidence: 79%
“…47 On the other hand, experiments in old mice have shown that full reconstitution of B-cell function is possible after irradiation with partial bone marrow shielding. 48 It seems likely, therefore, that a decline in B-cell output from the marrow is not a major determinant of impaired B-cell function in the elderly.…”
Section: B-lymphocyte Kinetics 3637mentioning
confidence: 99%
“…and bone marrow reconstituted the periphery together with T cells from young or aged donors. It was found that mice that received young T cells displayed auto-anti-idiotypic antibody profiles and a response to TNP-F like that of the young donor (61,62), whereas those that received aged T cells responded like the aged donors (61,62). These results strongly implicate the T cells in the quantity and quality of the immune response.…”
Section: Bone Marrow and Agingmentioning
confidence: 62%